Prominent Eustachian Valve in Newborns: A Report of Four Cases - Ashraf Gad; Javed Mannan; Manoj Chhabra; Xi Xiao Yang Zhang; Pramod Narula; Danthanh Hoang (Thieme Medical Publishers, Inc., 2016)
Abstract The Eustachian valve (EV) is an embryological remnant of the inferior vena cava that during fetal life helps divert oxygenated blood from the IVC toward the foramen ovale to escape the pulmonary circulation. This remnant usually regresses after birth and is considered a benign finding in the majority of cases. However, EV can lead to complications in the neonatal period or later in life. In this short case series, we present four newborn infants with prominent EV who were symptomatic after birth and required admission to the neonatal intensive care unit.